Effects of mixing late-finishing pigs just before marketing on growth performance - Potter, M. L.; Bergstrom, J. R.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 512 commercial finishing pigs were used in a 15-d trial to determine the effects of mixing late-finishing pigs from 1 or 2 barns at different stocking densities on pig performance prior to marketing. Close-to-market-weight pigs from 2 barns (north barn or south barn) were placed in 32 single-sex pens in the north barn at densities of either 12 or 20 pigs per pen. Pens of pigs were allotted to 1 of 4 mixing treatments (8 pens per treatment). Mixing treatments were: (1) nonmixed pens with 12 north barn pigs (control), (2) mixing 6 north barn pigs with 6 south barn pigs (Mix 1), (3) mixing 10 north barn pigs with 10 south barn pigs (Mix 2), and (4) mixing 10 north barn pigs with 10 more north barn pigs (Mix 3). All pigs were fed a common diet during the trial. Pens of pigs were weighed and feed disappearance determined on d 0, 8, and 15 to determine ADG, ADFI, and F/G. All response criteria were adjusted to a common initial weight in the analysis. Results from this trial indicate that pen inventories had a large impact on performance, with pigs stocked at 12 pigs per pen having greater ADG (P ≤ 0.06) and ADFI (P ≤ 0.02) than those stocked at 20 pigs per pen. Overall, there was no difference in performance for nonmixed control pigs and mixed pigs when stocked at a similar density (12 pigs per pen). These data indicate, in the 2 wk prior to market, increasing the number of pigs per pen had a larger effect on performance than mixing pigs. Although performance was negatively affected immediately after mixing, overall performance of mixed pigs was not different than that of nonmixed pigs. Therefore, given adequate time to adjust to a new environment and establish a new social order, mixing pigs does not appear to affect overall performance.
Keywords: Swine; Growth; Management at marketing; Mixing